Respuestas
Respuesta dada por:
1
(senA + cscA)² = sen²A + cot²A + 3
sabemos que:
cscA = 1 /senA
cotA = cosA /senA:
[senA + (1 /senA)]² = sen²A + (cosA /senA)² + 3
sen²A + 2senA (1 /senA) + (1 /senA)² = sen²A + (cos²A /sen²A) + 3
(partiendo el 3 en 1 + 2)
sen²A + 2 + (1 /sen²A) = sen²A + [(cos²A /sen²A) + 1] + 2
sen²A + 2 + (1 /sen²A) = sen²A + [(cos²A + sen²A)/sen²A] + 2
(aplicando la identidad fundamental cos²A + sen²A = 1)
sen²A + 2 + (1 /sen²A) = sen²A + (1 /sen²A) + 2
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años